Chinese researchers, scholarly communication behaviour and trust. Issue 1 (8th January 2016) - Nicholas, David; Xu, Jie; Xu, Lifang; Su, Jing; Watkinson, Anthony
Abstract: Over 660 Chinese researchers were questioned about their scholarly use, citing, and publishing and how trust is exercised in these key activities. Research showed few signs of new forms of scholarly usage behaviour taking hold, despite multiple opportunities afforded by Science 2.0 developments. Thus, for determining trustworthiness for usage purposes, the most important activity was reading the abstract. In terms of citations, citing the seminal source was the most common activity. In contrast, citing non‐peer reviewed sources, such as the social media, was not thought acceptable. For publishing, relevance to the field was the most important factor when choosing a place to publish. Comparisons were made with a study of 3650 international researchers, which employed the same methods and questions. The main differences between Chinese and international researchers were that the former (a) rated abstracts more highly, (b) took into account impact factors more when citing and publishing and (c) were much more likely to be influenced by institutional directives when placing their articles.